Modelando sistemas de informação gamiﬁcados: uma abordagem orientada a agentes e objetivos - Luiz Gustavo da Fonseca Ferreira (2019)
“People are the most valuable asset of a company” is perhaps the oldest cliché in the business world. Despite the importance of people for organizations and its process, traditional and popular modeling approaches abstract human factor and focus only on the “what” and “how” of a process, emphasizing the functional aspects of the system. Gamiﬁcation, as a persuasive technology, goes beyond the functional aspects, and by adding game elements in the user experience, seeks to inﬂuence the user to present certain behaviors considered to be desirable by the designer. Since Gamiﬁcation deals with human motivation, a gamiﬁcation designer frequently deals with the "why", seeking to understand the reasons and motivations behind the process. Without this comprehension, the analyst risks designing an ineﬀective gamiﬁcation experience, or even worse, an implementation that negatively aﬀects the user behavior. Despite the importance of the social and intentional aspects in the design and analysis of gamiﬁed applications, there is no modeling tool yet that covers those aspects and helps designers to eﬀectively incorporate them into the process of creating a gamiﬁcation concept to be implemented in a system. In this context, the objective of this work was to propose a method for modeling gamiﬁed applications that provides a structured representation of the social and intentional dimensions of the actors involved in the organizational context of the gamiﬁed system. To achieve this, the proposed approach (called GStar) was based on the agent-oriented and objective-oriented paradigms implemented in the modeling framework i*. The research problem was addressed according to the principles of the Design Science Research, and case studies were conducted to illustrate and validate the usefulness of the proposed method for the analysis, redesign, and design of gamiﬁed systems. The main contribution of this work is to bring the social and intentional aspects, which are usually treated in an ad hoc manner in the design of gamiﬁed systems, to the core of a new modeling approach. This approach supports the analysis of the consequences of the inclusion of each gamiﬁcation element and facilitates the evaluation by the designer of diﬀerent alternatives, contributing to a project more suitable to the organizational context and more capable of fulﬁlling the established goals.